Primary Sjögren Syndrome in Han Chinese. Issue 16 (April 2015) - Zhao, Yun; Li, Ya; Wang, Li; Li, Xiao-Feng; Huang, Ci-Bo; Wang, Guo-Chun; Zhang, Xue-Wu; Zhang, Zhuo-Li; Zhang, Xiao; Xiao, Wei-Guo; Dai, Lie; Wang, Yong-Fu; et al.
<x xml:space="preserve">Abstract</x> Abstract The epidemiological characteristics of Sjögren syndrome (SS) are significantly varied in different countries. We conducted the present study to survey the epidemiological characteristics of primary SS in China. We recruited 483 primary SS patients from 16 Chinese medical centers nationwide from January 2009 to November 2011 and assessed salivary and lacrimal gland dysfunction, organ involvement, and autoimmunity in these patients. The cohort included 456 women and 27 men (ratio, 17:1; mean age at onset, 42 ± 11 years; median age at diagnosis, 49 years; range, 41–56 years). Male patients showed a lower frequency of xerophthalmia (37.0% vs 60.7%) and a higher frequency of arthritis (40.7% vs 16.4%). Young-onset patients showed a higher frequency of low C3 levels (57.7% vs 36.3%) and pancytopenia (22.2% vs 8.8%). Patients with systemic involvement had a higher frequency of immunoglobulin A (IgA) (39.4% vs 22.5%) and immunoglobulin M (IgM) (12.4% vs 37.9%). Patients with pulmonary involvement had a higher parotid enlargement (21.4% vs 10.2%), purpura (12.1% vs 5.7%) and higher anti-La/SS-B (61.7% vs 41.8%), immunoglobulin G (IgG) (80.7% vs 64.6%) and IgA (48.9% vs 30.6%) levels. Patients with anti-Ro/SSA antibodies had more frequent exocrine gland symptoms and some extraglandular symptoms and immunological alterations. Compared with previous studies performed in other countries, SS patients in China showed particular clinical manifestation, systemic involvement, and immunological alterations.